Efektivitas Realitas Virtual sebagai Alternatif Terapi Keseimbangan Postur Tubuh Pasien Stroke Kronis - Ika Monita; Sandy Faisal (Jurnal Riset Kedokteran, 2022)
Abstract. Virtual reality is a technology that allows users to interact with an environment that only exists in imagination, but looks like real to the person who uses it. The right time to do virtual reality therapy is 6 months after stroke, which is a chronic phase or it can be a subacute phase but has already experienced stabilization. The purpose of this study was to analyze the effectiveness of virtual reality therapy in chronic stroke patients, and to compare the effectiveness of virtual reality in the experimental group and the control group. The study was conducted using the scoping review method, by searching for articles from the PubMed database with the keywords ("virtual reality Exposure Therapy"[Mesh]) AND "Postural Balance"[Mesh]) AND "Stroke"[Mesh]. Science Direct, Proquest, Google Scholar, Springer Link, with keywords “Virtual Reality” AND “Postural Balance” AND “Stroke”. Search for articles in the 2011-2021 range, in English, fully accessible, original research article type. There are 1441 articles that meet the inclusion criteria. There are 17 articles that meet the PICOS criteria, and 5 articles that meet the eligible criteria based on critical appraisal. The results of the study of 5 articles showed that of the 5 articles analyzed, research was carried out in the chronic phase. The average length of intervention from the 5 articles was 4.5 weeks. Hemorrhagic and ischemic stroke types from the 5 articles were randomly assigned to the experimental group and the control group. These characteristics correlate with exposure to virtual reality exercise, which affects the complex syndrome of chronic stroke which is then given a virtual reality repetitive task-oriented exercise, which triggers brain neuroplasticity. The movements of paresis of the limbs will also follow the limbs that perform virtual reality training activities. The results and conclusions show that virtual reality is proven to increase the effectiveness of posture balance in chronic stroke patients and its effectiveness is higher than the control group. Abstrak. Realitas virtual adalah teknologi yang memungkinkan pengguna berinteraksi dengan lingkungan yang hanya ada dalam imajinasi, tetapi terlihat seperti nyata bagi orang yang menggunakannya. Waktu yang tepat untuk melakukan terapi virtual reality adalah 6 bulan setelah stroke yang merupakan fase kronis atau bisa juga fase subakut tetapi sudah mengalami stabilisasi. Tujuan dari penelitian ini adalah untuk menganalisis efektivitas terapi virtual reality pada pasien stroke kronis, dan membandingkan efektivitas virtual reality pada kelompok eksperimen dan kelompok kontrol. Penelitian dilakukan dengan metode scoping review, dengan mencari artikel dari database PubMed dengan kata kunci ("virtual reality Exposure Therapy"[Mesh]) DAN "Postural Balance"[Mesh]) DAN "Stroke"[Mesh]. Science Direct, Proquest, Google Scholar, Springer Link, dengan kata kunci “Virtual Reality” DAN “Postural Balance” DAN “Stroke”. Cari artikel dalam rentang 2011-2021, dalam bahasa Inggris, dapat diakses sepenuhnya, jenis artikel penelitian asli. Ada 1441 artikel yang memenuhi kriteria inklusi. Terdapat 17 artikel yang memenuhi kriteria PICOS, dan 5 artikel yang memenuhi kriteria layak berdasarkan penilaian kritis. Hasil kajian 5 artikel menunjukkan bahwa dari 5 artikel yang dianalisis, penelitian dilakukan pada fase kronis. Rata-rata lama intervensi dari 5 artikel adalah 4,5 minggu. Jenis stroke hemoragik dan iskemik dari 5 artikel secara acak ditugaskan ke kelompok eksperimen dan kelompok kontrol. Karakteristik ini berkorelasi dengan paparan latihan realitas virtual, yang mempengaruhi sindrom kompleks stroke kronis yang kemudian diberikan latihan berorientasi tugas berulang realitas virtual, yang memicu neuroplastisitas otak. Gerakan paresis tungkai juga akan mengikuti tungkai yang melakukan aktivitas latihan virtual reality. Hasil dan kesimpulan menunjukkan bahwa virtual reality terbukti meningkatkan efektivitas keseimbangan postur pada pasien stroke kronis dan efektivitasnya lebih tinggi daripada kelompok kontrol.